A case of cutaneous myiasis caused by Wohlfahrtia magnifica - Kokcam, I; Saki, CE (Japanese Dermatolgical Assoc, 2005)
Myiasis is caused by the invasion of tissues or organs of man or animals by dipterous larvae. The disease is infrequent in Turkey; it is observed particularly in people with some predisposing factors. A 46-year-old male farmer with nevoid basal cell carcinoma syndrome (NBCCS) presented with the complaint of a blood-tinged discharge and pain in the left frontal-temporal region for three days. Physical examination revealed live maggots in the ulcerous wound resulting from basal cell carcinoma. The larvae were removed with forceps, and the wound was locally dressed with povidone-iodine. The maggots were identified as the third instar larvae of Wohlfahrtia magnifica.
Keywords: cutaneous myiasis; Wohlfahrtia magnifica; nevoid basal cell carcinoma; syndrome